Pengetahuan, Peran Orang Tua dan Persepsi Remaja terhadap Preferensi Usia Ideal Menikah - M. Taufik; Harni Sutiani; Andri Dwi Hernawan (Poltekkes Kemenkes Pontianak, 2018)
Abstract: Knowledge, Parental Roles, And Adolescents Perception Toward Preference Of Ideal Age Of Marriage . Marriage is a bond born of inner and between a man and a woman as the husband and wife with the aim of forming a happy family and eternal. Necessary preparations towards domestic life. Age is one of the most important considerations to get married, as it associates with maturity and proper relation-ship to commit someone’s life to someone else. Right age is also essential to determine the physical, mental, and financial readiness. This study aimed at de-termining the correlation of knowledge on maturity in marriage , parental roles, perception on early marriage, and the preference of ideal age of marriage in Kecamatan Sungai Raya, Kabupaten Kubu Raya. Using cross sectional ap-proach, 240 adolescents aged 15-19 years participated in this study. This study was conducted from October-December 2016. The samples were selected by us-ing rapid survey method. The data were analyzed and processed through computerization, and statistically tested by using chi square test. The study shows that there were correlations of knowledge on maturity in marriage (p-value = 0,003), parental roles (p value = 0,002) and perception on early marriage (p val-ue = 0.037) with ideal age of marriage. From the findings, students are encour-aged to take part in positive activities such as boy scouts, the red cross youth, adolescent counseling and information center, and mosque teens, for parents can follow youth community development to provide information that is complete and correct to the teens about the growth and development of adolescents as well as premarital preparation, National Population and Family Planning Board (BKKBN) need to work together to control and reduce the number of early.Abstrak: Pengetahuan, Peran Orang Tua Dan Persepsi Remaja Terhadap Preferensi Usia Ideal Menikah. Perkawinan adalah ikatan lahir batin antara seorang pria dan wanita sebagai suami istri untuk membentuk keluarga bahagia dan kekal. Diperlukan persiapan menuju kehidupan rumah tangga. Salah satunya adalah usia yang tepat, hal ini dimaksudkan agar siap dan matang dari segi fisik, psikis, mental dan ekonomi. Penelitian bertujuan mengetahui hubungan antara pengetahuan tentang pendewasaan usia perkawinan, peran orang tua dan persepsi tentang per-nikahan usia dini dengan preferensi usia ideal menikah remaja di Kecamatan Sungai Raya Kabupaten Kubu Raya. Penelitian menggunakan pendekatan cross sectional dengan jumlah sampel 240 remaja usia 15–19 tahun yang dilaksanakan bulan Oktober–Desember 2016. Teknik pengambilan sampel menggunakan metode survey cepat. Pengolahan dan analisis data menggunakan komputerisasi. Uji Statistik menggunakan uji chi square. Hasil penelitian menunjukkan ada hubungan antara pengetahuan tentang pendewasaan usia perkawinan (p value = 0,003), peran orang tua (p value =0,002) dan persepsi tentang pernikahan usia dini (p value = 0,037) dengan preferensi usia menikah remaja. Remaja disarankan mengikuti kegiatan seperti pramuka, PMR, remaja masjid, PIK Remaja, bagi orang tua dapat mengikuti Bina Keluarga Remaja agar memberikan informasi lengkap dan benar tentang pertumbuhan dan perkembangan remaja serta persiapan pranikah, BKKBN dan instansi terkait bersinergi dalam menekan terjadinya angka pernikahan pada usia tidak ideal.